2011
DOI: 10.1007/s11814-010-0434-x
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of polymer multilayer thin films for novel biomedical applications

Abstract: The design of functional polymer multilayer thin films with nanometer scale control is of great interest for biomedical applications such as tissue engineering, targeted drug delivery, controlled release system, and regenerative medicine. Various functions and properties of polymer thin films can be easily programmed and realized by the layer-by-layer assembly strategy, which is a facile and versatile deposition method to prepare well-defined biomedical multilayer platforms due to its benign process to prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…Conversely, models can be selected based on the length scale of the phenomena of interest. The correct prediction of biopolymer network mechanical/rheological properties is important in many biomedical applications associated with biopolymer networks [1,130,131]. Therefore, the framework provided by this review is expected to promote various studies on biopolymer networks.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, models can be selected based on the length scale of the phenomena of interest. The correct prediction of biopolymer network mechanical/rheological properties is important in many biomedical applications associated with biopolymer networks [1,130,131]. Therefore, the framework provided by this review is expected to promote various studies on biopolymer networks.…”
Section: Discussionmentioning
confidence: 97%
“…GO multilayer films were deposited on the Ti substrates by layer-by-layer (LbL) assembly. 34,35 Briefly, the substrates were then dipped for 10 minutes in the cationic GO-NH 3 + solution, washed three times by dipping in deionized water for 1 minute, and then dried with a gentle stream of nitrogen. The negatively charged GO-COO − was subsequently deposited onto the GO-NH 3 + coated films using the same adsorption, washing, and drying procedures described above.…”
Section: Multilayer Coatings Of Ti Substrates With Gomentioning
confidence: 99%
“…29,34,35 Coating with multiple layers of GO resulted in a full coverage of the Ti substrate ( Figure 1A). Atomic force microscopy revealed that, unlike the bumpy surface of an uncoated Ti substrate, the GOcoated Ti surfaces became much smoother after multiple cycles of LbL deposition.…”
Section: Coating Of Ti Substrates With Gomentioning
confidence: 99%
“…Suitably engineered polyelectrolyte multilayers (PEMs) have long been recognized as versatile biomaterial platforms due to their similarity to naturally occurring, highly hydrated systems, ease of biochemical functionalization, high level of biocompatibility and tunable mechanical compliance [30][31][32][33][34]. These attributes can be realized with synthetic polymers, and more importantly, with naturally occurring polymers, including DNA, polypeptides and polysaccharides.…”
Section: Living Cells As Functional Elements Of Polyelectrolyte Multimentioning
confidence: 99%